Moral Woman and Immoral Society: Schleiermacher on Female and Male - Nicol, Iain G. (Toronto journal of theology, 1985)
The primary purpose of the following brief analysis is to examine some of Schleiermacher's statements on the subject of the relationships between male and female and to explore some implications of this aspect of his thought in their relation to the consistent emphasis in his philosophical and theological ethics on a social theory of part and whole.